Determining factors of school failure in Spain: A socio-educational analysis of knowledge production - Moles-López, Elisabet; Añaños, Fanny T-; Burgos Jiménez, Rubén J. (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: this research analyzes the factors that determine school failure in Spain, based on the “Encuesta Social de 2010: Educación y hogares en Andalucía”. From which, we use a representative sample of 5032 cases. Originality/contribution: School failure is a current topic of great interest in socio-educational research, as well as a priority objective to be addressed in the agenda of the European Union due to the high rates registered in recent years. Method: it is based on a systematic documentary analysis from a quantitative approach. Strategies/information collection: by exploiting secondary data from the survey, we make inference with the current situation using two binary logistic regression models by age cohorts. The results show a gender gap in the probability of school failure. Women show a lower risk. The socio-family level indicates that the importance parents/tutors give to education is not a factor related to school failure. However, parental control on secondary education studies decreases its probability. The socioeconomic status of the family appears as an incident factor. Conclusions: The findings highlight the need for adequacy and updating of data on the factors that determine school failure from a socio-educational and gender perspective. This would allow a socio-educational intervention and the creation of educational-social policies coherent with the social reality, which attend to the specific characteristics and conditions of the student body, to prevent school failure, promote integral development and social integration.